Innovative Curriculum within a New Zealand Low Decile Secondary School: A Case Study - Soysa, Tara-Lee (Auckland University of Technology, 2019)
The Ministry of Education has expressed a desire to develop twenty-first century learners through innovative approaches to the New Zealand curriculum, indicating that a move away from traditional subject specific educational practice is envisioned. This study was established through my sense that innovative curriculum practices could be more engaging for today’s students and could support increases in academic achievement, particularly for students whose communities experience socio-economic hardship. I sought to understand what senior curriculum innovation could look like in a secondary school, while critically examining the practices and leadership required for such implementation in a low decile context. As a former student of a low decile school and as an aspiring secondary school principal with ten years’ experience teaching visual arts in low decile environments, this study aimed to enhance my own teaching and leadership practice. My research was conducted through a single instrumental case study approach that utilised four semi-structured interviews to collect perspectives of school leaders, teachers and students. This data was used to illustrate and provide insight into my research school’s context, its innovative curriculum pedagogies, practices and implementation approaches. My small qualitative study was underpinned by an interpretive paradigm that recognises and acknowledges the strengths in gathering participant’s perceptions and experiences to formulate qualitative research. Furthermore, by illustrating this single context, my research intends to highlight some of the perceived barriers to innovative curriculum while understanding what it means to be successful in being innovative. My study revealed that while this high school had started to significantly shift its curriculum pedagogy alongside traditional constraints such as timetabling, traditional notions and expectations of senior secondary schooling, particularly an over-emphasis on students gaining achievement standards still hindered extensive implementation of innovative senior curriculum design and delivery. All participants emphasised the importance of leadership in encouraging sustained innovative learning environments. The predominant senior leader perspective in my study considered that developing collaborative leadership models that seek to disestablish traditional hierarchies is an effective leadership approach for implementing innovative curriculum. These leadership concepts along with the struggles of implementing new teaching and learning practice was also evident in my reviewed literature. Although this study provided a deeper insight into a single context, this research area of innovative curriculum could benefit from more examples and studies being conducted in more New Zealand secondary school contexts, particularly those from low decile communities.
Keywords: Curriculum innovation; New Zealand senior high school curriculum; NCEA; Cross-curricular